Enfermedades laborales en empresas mineras a pequeña escala en Colombia: un análisis de los desafíos y oportunidades para la prevención y protección de los trabajadores mineros. (2023)
This monograph was carried out with the objective of investigating which are the most recurrent occupational diseases in small-scale mining within the department of Cundinamarca, in order to compile available information from the last 10 years, from the different studies carried out by different public entities. such as the Government of Cundinamarca, the Ministry of Labor, the National Mining Agency; the academy “university research”; mining sector associations and other publications of a particular type "blogs, internet pages, videos, etc.", in order to determine good practices and recommendations for the health of workers in small-scale mining.